Nicoladoni-Branham Sign in the Coronaries: Fistula Closure Leads to Immediate Relief - Mouna Kodali; A. Jamil Tajik; Suhail Q. Allaqaband; Nancy Barrett; Khawaja Afzal Ammar (Annals of Internal Medicine: Clinical Cases)
We describe the first reported case, to our knowledge, of Nicoladoni-Branham sign in a patient with a large right coronary artery to superior vena cava fistula presenting with high-output heart failure. Percutaneous closure of the fistula resulted in immediate symptomatic relief and resolution of sinus tachycardia. It is important to recognize this physiologic mechanism not only to resolve high-output heart failure but also to relieve patients from years of unrelenting dyspnea, palpitations, and discomfort.